2017
DOI: 10.11648/j.avs.20170502.12
|View full text |Cite
|
Sign up to set email alerts
|

Pre and Post-natal Nutrition of Ewes on the Performances of Native Bengal Ewes and Their Lambs

Abstract: Abstract:The aim of the study is to determine the effects of different plane of nutrition during late pregnancy to lactation on the performances of ewes and their offspring to weaning. About 36 native Bengal ewes of last 7 weeks gestation were randomly assigned to four different groups (T 0 , T 1 , T 2 , T 3 ). The T 0 , T 1 , T 2 and T 3 groups were supplemented a concentrate mixture at 0.0, 1.0, 1.5 and 2.0% of their body weight, respectively. Chopped German grass (Echinochloa polystachya) was provided as ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…The higher weaning weight of lamb depends on birth weight and daily milk yield of ewes i.e. the pre and post-natal nutrition of ewes (Ahmed et al, 2017). Although, ewes post-partum heat period did not significantly affect by different plane of nutrition but it reduced with the increased supplementation of concentrate that helps to reduce kidding interval (Ahmed et al, 2017).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The higher weaning weight of lamb depends on birth weight and daily milk yield of ewes i.e. the pre and post-natal nutrition of ewes (Ahmed et al, 2017). Although, ewes post-partum heat period did not significantly affect by different plane of nutrition but it reduced with the increased supplementation of concentrate that helps to reduce kidding interval (Ahmed et al, 2017).…”
Section: Resultsmentioning
confidence: 97%
“…Milk yield of ewe is the main factor affecting lamb growth during the first few weeks of life and are highly correlated during the 4-6 weeks of age (Owen, 1976). Several researchers like Susin et al (1995) for Polypay ewes, El-Shakhretet et al (1996) for Jordanian Awassi ewes, Shams al-dain et al (2003) for Iraqi Awassi ewes Aziz and Al-Dabbagh (2008) for Hamandi ewes and Ahmed et al, (2017) in native Bengal ewes, were also reported that milk yield was affected by plane of nutritional before and after lambing. In supporting the above findings by different authors, the present study observed a strong positive linear relationship (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Jamuna basin, Barind tract and coastal belt sheep have the great potentiality for profitable lamb production that might fulfil the meat requirement, livelihood improvement and sustainable earning option. Lacks of public awareness, misconception about sheep meat (lamb/mutton), and inadequate nutrition supplementation are the limiting factors for sheep farming in Bangladesh (Ahmed et al, 2017). Under traditional feeding systems, sheep are raised on harvested or fallow lands, roads, and canal sides and also grazed on aquatic weeds and grass in knee-deep water without any supplementation (Sultana et al, 2010).…”
Section: Introductionmentioning
confidence: 99%